Serum growth differentiation factor 15 as a biomarker for malnutrition in patients with acute exacerbation of chronic obstructive pulmonary disease - Shi, Guifen; Yue, Longfei; Tang, Zhengying; Wang, Yingling; Hu, Xiwei; Tong, Yufeng (Frontiers in Nutrition, 2024)
Background Chronic obstructive pulmonary disease (COPD) is a common respiratory disease that often coexists with malnutrition during acute exacerbation (AECOPD) and significantly affects the prognosis. Previous studies have shown that growth differentiation factor 15 (GDF15) levels promote appetite suppression, weight loss, and muscle weakness, and are markedly high in peripheral blood following inflammatory stimulation. However, it is still unknown whether serum GDF15 levels can be used to predict malnutrition in patients with AECOPD. Methods A total of 142 patients admitted to the Department of Respiratory Medicine at Anshun People’s Hospital between December 2022 and August 2023 were selected for this study. The participants were divided into two groups: malnutrition group (n = 44) and non-malnutrition group (n = 98) based on a body mass index (BMI) < 18.5 kg/m2, according to the Global Leadership Initiative on Malnutrition (GLIM) criteria. Serum GDF15 levels were measured using the enzyme-linked immunosorbent assay (ELISA) and compared between the two groups. Spearman correlation analysis was used to examine the association between serum GDF15 levels, baseline data, and clinical indicators. Binary logistic regression was used to identify the independent risk factors for AECOPD combined with malnutrition. The predictive value of serum GDF15, albumin (ALB), and a combination of these was evaluated to identify malnutrition in patients with AECOPD using a receiver operating characteristic (ROC) curve. Results Serum GDF15 levels in patients with malnutrition and AECOPD were significantly higher than those in patients without malnutrition, whereas the serum ALB levels were significantly lower than those in patients without malnutrition (p < 0.001). Moreover, serum GDF15 levels were negatively correlated with BMI (r = −0.562, p < 0.001), mid-arm circumference (r = −0.505, p < 0.001), calf circumference (r = −0.490, p < 0.001), total protein (r = −0.486, p < 0.001), ALB (r = −0.445, p < 0.001), and prognostic nutritional index (r = −0.276, p = 0.001), and positively correlated with C-reactive protein (r = 0.318, p < 0.001), COPD assessment test score (r = 0.286, p = 0.001), modified medical research council classification (r = 0.310, p < 0.001), and global initiative for chronic obstructive pulmonary disease grade (r = 0.177, p = 0.035). Furthermore, serum GDF15 levels were an independent risk factor for malnutrition in patients with AECOPD (OR = 1.010, 95% CI, 1.003∼1.016). The optimal cut-off value of serum GDF15 level was 1,092.885 pg/mL, with a sensitivity of 65.90% and a specificity of 89.80%, while the serum ALB level was 36.15 g/L, with a sensitivity of 86.40% and a specificity of 65.00%, as well as a combined sensitivity of 84.10% and a specificity of 73.90%. Serum GDF15 and serum ALB levels had a good predictive ability (AUC = 0.856, AUC = 0.887), and the ROC revealed a greater combined prediction value for the two (AUC = 0.935). Conclusion Serum GDF15 levels could be used as a potential biomarker in the prediction of malnutrition in patients with AECOPD, offering a guidance for future clinical evaluation of malnutrition.